2005
DOI: 10.4049/jimmunol.175.2.1239
|View full text |Cite
|
Sign up to set email alerts
|

CD93 Is Rapidly Shed from the Surface of Human Myeloid Cells and the Soluble Form Is Detected in Human Plasma

Abstract: CD93 is a highly glycosylated transmembrane protein expressed on monocytes, neutrophils, endothelial cells, and stem cells. Antibodies directed at CD93 modulate phagocytosis, and CD93-deficient mice are defective in the clearance of apoptotic cells from the inflamed peritoneum. In this study we observe that CD93, expressed on human monocytes and neutrophils, is susceptible to phorbol dibutyrate-induced protein ectodomain shedding in a time- and dose-dependent manner. The soluble fragment found in culture super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
87
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 30 publications
9
87
0
Order By: Relevance
“…More recently, it was reported that CD93 expressed on monocytes and neutrophils is susceptible to phorbol dibutyrate (PDBu)-induced protein ectodomain shedding and that the soluble fragment in human plasma retains the N-terminal carbohydrate recognition domain and the EGF repeats (1). In addition, this report indicated that PDBu-induced CD93 shedding on monocytes was accompanied by a decrease in CD93 cell surface expression, whereas neutrophils displayed an increase in cell surface expression and CD93 shed from the neutrophil surface was rapidly replaced by CD93 from intracellular stores (1). These data, including that from our study, strongly indicate that CD93 has physiological roles in various immune responses.…”
Section: Discussionsupporting
confidence: 71%
“…More recently, it was reported that CD93 expressed on monocytes and neutrophils is susceptible to phorbol dibutyrate (PDBu)-induced protein ectodomain shedding and that the soluble fragment in human plasma retains the N-terminal carbohydrate recognition domain and the EGF repeats (1). In addition, this report indicated that PDBu-induced CD93 shedding on monocytes was accompanied by a decrease in CD93 cell surface expression, whereas neutrophils displayed an increase in cell surface expression and CD93 shed from the neutrophil surface was rapidly replaced by CD93 from intracellular stores (1). These data, including that from our study, strongly indicate that CD93 has physiological roles in various immune responses.…”
Section: Discussionsupporting
confidence: 71%
“…For example, thrombomodullin is expressed in endothelial cells and has anticoagulant activity resulting from sequestration of thrombin and activation of protein C (Maruyama et al, 1985;Esmon, 1995). CD93 is expressed in endothelium, cells of myeloid lineage and stem cells (Bohlson et al, 2005). Although not expressed by endothelium (MacFadyen et al, 2005), TEM1/endosialin mediates tumor, but not developmental angiogenesis.…”
Section: Clec14a Is a Novel Tumor Endothelial Markermentioning
confidence: 99%
“…This suggested that sCD93 was proteolytically cleaved from the surface-bound form (7). Further studies showed that CD93 was rapidly shed from the surface of human myeloid cells, and sCD93 was detected in human plasma (21,22). Additionally, Greenlee et al (23) demonstrated production of sCD93 in vivo under inflammatory conditions.…”
mentioning
confidence: 98%
“…Recently, two separate studies reported the identification of a soluble form of CD93 (sCD93) (7,21). Initially, it was demonstrated that hypoglycosylation of CD93 caused an increase in the levels of sCD93 in culture medium.…”
mentioning
confidence: 99%